(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: The influence of non-alcoholic fatty liver disease (NAFLD) and metabolic syndrome (MS) in the antiviral treatment of patients with chronic hepatitis B (CHB) is still unclear in the literature. The increased prevalence of these comorbidities in the general population may influence the antiviral response in patients with CHB. Objectives: Evaluate the influence of NAFLD and MS on the complete virological response (CVR) time in patients with CHB. Methods: Retrospective cross-sectional study in which patients with CHB were divided into two groups: without comorbidities (G1) and with NAFLD and/or MS (G2). After describing their clinical, epidemiological and biochemical characteristics, we evaluated the groups in two moments, at the beginning of antiviral therapy and at the moment when CVR was reached, comparing the time in months for both groups until negative results. Results: 65 patients were evaluated after exclusion criteria (G1:48; G2:17). After describing the population, it was possible to assess the profile of patients in the population and found a mean time until CVR in G1 of 10.5 months and in G2 of 14 months (p=0.019). Conclusion: The presence of NAFLD and/or MS delays the complete virological response in individuals being treated for chronic hepatitis B. The joint assessment of these comorbidities may benefit the therapeutic response in individuals with chronic hepatitis B.